Tri-primary-color OLED device based on organic single-crystal dual-functional layer and preparation method thereof
By using organic single crystal semiconductor materials as dual-function layers for charge transport and water-oxygen barrier in OLED devices, the problem of insufficient efficiency and stability of the charge transport layer in traditional OLED devices is solved, and high efficiency and long-life red and green are achieved Blue three primary color OLED device.
Patent Information
- Application Number
- CN202411511724.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The low mobility and unstable surface morphology of the charge transport layer in existing OLED devices lead to insufficient device efficiency and stability, and the charge transport layer film prepared by traditional processes is sensitive to water and oxygen and is easy to degrade.
Organic single crystal semiconductor material is used as a dual-function layer for charge transport and water-oxygen barrier. Organic single crystal material is grown through physical gas phase transfer method, and hydrophobic treatment and water vapor transmittance test are carried out on the substrate to form a three-primary color of red, green and blue. OLED devices.
It improves the current efficiency and stability of OLED devices, achieves high carrier mobility and excellent water-oxygen barrier properties, and extends the device life.
Smart Images

Figure CN119403413A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic light emitting diode device preparation, and in particular to a three-primary color OLED device based on an organic single crystal double-functional layer and a preparation method thereof. Background Art
[0002] Organic light-emitting diode (OLED) devices have made great progress in the past few decades and have been commercialized in the fields of flat panel display and solid-state lighting. With the growing demand for display and lighting, higher requirements are placed on the efficiency and stability of OLED devices. Among the various functional layers in the OLED structure, the charge transport layer (CTL), as a key component for charge carrier injection and transport, plays a vital role in determining device performance. Usually, the charge transport layer obtained by OLED through traditional vacuum thermal evaporation or solution deposition is amorphous, which has a low carrier mobility, generally 10 -4 ~10 -6 cm 2 V -1 s -1The order of magnitude, so the thickness of the charge transport layer in the OLED structure is strictly controlled to tens of nanometers to ensure the effective transfer of charges inside the device. On the other hand, amorphous films usually have a rough surface, which makes the adhesion between the electrode and the organic layer poor, and the electrode also presents an uneven morphology, which will lead to pinholes for water vapor and oxygen penetration and electrode peeling, thereby affecting the stability of the device. A feasible solution is to use a thicker CTL to solve the above problems by more evenly covering the substrate and improving the surface morphology. However, the thick CTL inevitably produces a high driving voltage due to its low mobility and generates Joule heat, thereby accelerating the aging of the device. It has been reported that a two-micron thick perovskite film is used as a CTL in an OLED, and the low driving voltage is maintained by the high mobility of the perovskite. However, the rough surface, specific manufacturing process and poor stability of polycrystalline perovskite films limit their application in commercial OLEDs. In addition, a one-micron-thick amorphous organic film is also used as a CTL, and a specific ohmic contact needs to be formed by building a multilayer structure between the light-emitting layer and the electrode to satisfy the injection of carriers into the device, which means that the choice of materials is quite limited. The charge transport layer film prepared by traditional processes usually exhibits a loose and amorphous structure, which is extremely sensitive to water and oxygen, and is easily degraded by water and oxygen corrosion, resulting in failure of the charge transport layer material, thereby limiting the efficiency and stability of OLED devices. In practical applications, OLED devices usually need to be encapsulated, such as using atomic layer deposition (ALD) to deposit a water and oxygen barrier layer on the outside of the OLED to prevent the device from being corroded by water and oxygen. Therefore, a CTL with high mobility, smooth interface morphology, and high water and oxygen tolerance is very necessary for the high efficiency and long-term stability of OLEDs.
[0003] Organic single-crystal semiconductor (OSC) materials have long-range ordered molecular arrangements and low impurity content, which give them excellent charge transport properties. The highest carrier mobility reported for rubrene-based single-crystal transistors is close to 43 cm 2 V -1 s -1 , which is several orders of magnitude higher than the mobility of amorphous films, making OSC an ideal candidate for CTL. Unlike amorphous or polycrystalline films with rough, loose and uneven morphologies, OSC has outstanding properties from the perspective of its morphology, such as uniform thickness and ultra-smooth surface at the atomic level, which is very suitable for achieving uniform deposition of thin films. In addition, the tight molecular stacking in OSC can hinder the penetration of water vapor and oxygen, and act as an encapsulation for the device, which will be beneficial to the long-term stability of OLEDs. The high mobility, smooth interface morphology and excellent water and oxygen barrier characteristics of OSC demonstrate its great potential as a CTL, providing a feasible solution for achieving high-efficiency and high-stability OLEDs. Summary of the invention
[0004] The purpose of the present invention is to provide a three-primary color OLED device based on an organic single crystal dual-functional layer and a preparation method thereof, wherein an organic single crystal semiconductor material replaces a traditional evaporated amorphous film, a red, green and blue three-primary color luminescent film is used as a luminescent layer, and the high mobility and excellent water and oxygen barrier performance of the organic single crystal play the dual functional layer role of a charge transport layer and a water and oxygen barrier layer in the device, thereby improving the current efficiency and stability of the OLED device.
[0005] To achieve the above object, the present invention provides a method for preparing a three-primary-color OLED device based on an organic single crystal dual-functional layer, comprising the following steps:
[0006] S1. Growth and preparation of organic single crystals. 3-5 mg of organic single crystal material powder is placed in the high-temperature sublimation area of the dual-temperature zone quartz tube furnace. Then, high-purity argon gas is introduced into the tube furnace as a carrier gas to transport the sublimated material to the crystallization area. The temperature of the high-temperature sublimation zone and the low-temperature crystallization zone of the tube furnace, as well as the growth time, are set to start growing the organic single crystal material. After growth based on the physical vapor transport method, a thin sheet of organic single crystal material is obtained on the quartz tube wall.
[0007] S2, substrate pretreatment, after the substrate is ultrasonically cleaned with a cleaning agent, the solvent on the surface is blown away with high-pressure nitrogen, and then the cleaned substrate is placed in a culture dish, a hydrophobic modifier is dripped in the center of the culture dish, and the culture dish cover is closed, and the culture dish is placed in a vacuum oven to volatilize the hydrophobic modifier by heat and perform surface hydrophobic treatment on the substrate, and the treated substrate is taken out and ultrasonically cleaned with a cleaning agent again, and the solvent is blown away with high-pressure nitrogen and then set aside;
[0008] S3, water vapor permeability test of organic single crystal material, the thin sheet organic single crystal material grown in step S1 is transferred to the substrate pre-treated by hydrophobic treatment in step S2 with tweezers, and then the substrate with the organic single crystal attached is placed in a vacuum evaporation apparatus, Ca electrode is evaporated on the organic single crystal material through a mask, and then the mask is replaced, Ag electrodes are evaporated on both sides of the Ca electrode, so that the Ag electrodes on both sides are connected through the middle Ca electrode, the substrate is taken out of the vacuum evaporation apparatus, and photoresist is dripped on the surface of the substrate and covered with a transfer glass sheet for pressing, after the photoresist diffuses and covers the entire substrate, the substrate is placed under ultraviolet light for exposure to solidify the photoresist, and then the device is peeled off from the hydrophobic substrate with a blade and transferred to the glass substrate, the organic single crystal material can cover the Ca electrode and encapsulate it, the conductivity of the Ca electrode is tested under constant temperature and humidity conditions, and the water vapor permeability of the organic single crystal material is calculated;
[0009] S4. Preparation of red, green and blue primary color OLED devices based on organic single crystal charge transport layer. The thin sheet organic single crystal material grown in step S1 is transferred to the hydrophobic pretreated substrate in step S2 with tweezers, and the substrate with organic single crystal is covered with an organic layer mask, and placed in a vacuum evaporator. The light-emitting layer, hole blocking layer and electron transport layer are deposited on the organic single crystal material by vacuum thermal evaporation in sequence, and the cathode mask is replaced to continue to deposit the cathode. The device is taken out of the vacuum evaporator, and photoresist is dripped on the surface of the device and covered with a transfer glass sheet to press tightly. After the photoresist diffuses and covers the entire device, the device is exposed to ultraviolet light to solidify the photoresist. Subsequently, the device is peeled off from the hydrophobic substrate with a blade and transferred to a glass substrate. The device is then covered with an anode mask and placed in a vacuum evaporator. The hole injection layer and the anode are evaporated in sequence to complete the preparation of the entire device.
[0010] Preferably, in step S1, the organic single crystal material is a p-type organic single crystal semiconductor material, which serves as a hole transport layer of the OLED device.
[0011] Preferably, the organic single crystal material is one of 1,4-bis(4-methylphenylvinyl)benzene (BSB-Me), 2,6-diphenylanthracene (DPA), and 2,5-bis(4-biphenyl)thiophene (BP1T).
[0012] Preferably, in step S1, the temperature of the sublimation zone and the crystallization zone of the dual-temperature zone tubular furnace are 270-380° C. and 240-340° C. respectively, the growth time is 2-3 hours, and the flow rate is 30-40 mL / min.
[0013] Preferably, in step S2, the substrate is a single-sided polished Si substrate with a size of 1.4 cm×1.6 cm, the cleaning agents are acetone, ethanol and isopropanol, the hydrophobic modifier is octadecyltrichlorosilane (OTS), the modification temperature is 60° C., the time is 4 hours, and the vacuum degree of the vacuum oven is 0.1 MPa.
[0014] Preferably, in step S3, the Ca electrode evaporation rate is The evaporation rate of Ag electrode is The exposure and curing time of the photoresist under UV light is 15-20 minutes.
[0015] Preferably, in step S4, the light-emitting layer comprises red, green and blue primary color organic light-emitting materials and a main body material; the hole blocking layer is 2-(4-(dibenzo[b,d]thiophene-4-yldiphenylsilyl)phenyl)-4,6-diphenyl-1,3,5-triazine (BTSiTrz), 2-(3'-(9,9-dimethyl-9H-fluorene-2-yl)-[1,1'-biphenyl]-3-yl)-4,6-diphenyl The electron transport layer is one of 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 4,7-diphenyl-1,10-phenanthroline (BPhen), 3,3'-[5'-[3-(3-pyridyl)phenyl][1,1':3',1"-terphenyl]-3,3"-diyl]bipyridine (TmPyPB), and the evaporation rate is The cathode is a Ca / Ag composite electrode, and the evaporation rates are and The hole injection layer is MoO3, and the evaporation rate is The anode is a composite electrode of Au and Ag, and the evaporation rate is
[0016] Preferably, the red light organic light-emitting material is bis(2-methyldibenzo[F,H]quinoxaline)(acetylacetonate)iridium(III))(Ir(MDQ)2(acac)), the green light organic light-emitting material is acetylacetonate di(2-phenylpyridine-C2,N)iridium(III))(Ir(ppy)2(acac)), the blue light organic light-emitting material is di(4,6-difluorophenylpyridine-C2,N)pyridinecarboxylateiridium(III))(FIrPic), the host material is one of 4,4'-bis(N-carbazole)-1,1'-biphenyl (CBP), 1,3-bis(N-carbazolyl)benzene (mCP), and 9-(3-(9H-carbazole-9-yl)phenyl)-9H-3,9'-dicarbazole (mCBCP), and the red, green, and blue organic light-emitting materials are doped in the host material at a mass ratio of 1% to 5%, respectively, to prepare an organic phosphorescent film as a light-emitting layer.
[0017] The three-primary-color OLED device based on an organic single crystal double-functional layer is prepared by a preparation method of a three-primary-color OLED device based on an organic single crystal double-functional layer.
[0018] The advantages and beneficial effects of the three-primary-color OLED device based on the organic single crystal dual-functional layer and the preparation method thereof are as follows:
[0019] The present invention proposes a method for preparing a red, green and blue three-primary color OLED device by using an organic single crystal semiconductor material as a dual-functional layer for charge transmission and water and oxygen barrier. The high carrier mobility of the organic single crystal semiconductor material realizes efficient carrier transmission capability in the OLED device, thereby improving the electroluminescent efficiency of the OLED. The tight molecular stacking inside the organic single crystal can effectively block water and oxygen, and has a packaging effect on the device, thereby improving the stability of the device.
[0020] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The present invention is based on the water vapor transmission rate test of BSB-Me organic single crystal material, wherein (a) is a device structure diagram of calcium corrosion electrical test, and (b) is a curve of normalized conductivity change of calcium electrode over time;
[0022] Figure 2 1 is a structural diagram of a red, green and blue three-primary color OLED device based on a BSB-Me organic single crystal dual-functional layer of the present invention, wherein (a) is a red light device, (b) is a green light device, and (c) is a blue light device;
[0023] Figure 3 1 is a performance spectrum of the red, green and blue primary color OLED device of Example 1 of the present invention, wherein (a) is a current density-voltage relationship diagram, (b) is a brightness-current density relationship diagram, (c) is a current efficiency-current density relationship diagram, and (d) is an external quantum efficiency-brightness relationship diagram;
[0024] Figure 4 1 is a brightness decay curve of the red, green and blue three-primary color OLED device at different initial brightnesses according to Example 1 of the present invention, wherein (a) is a red light device, (b) is a green light device, and (c) is a blue light device;
[0025] Figure 5 1 is a curve showing the change in LT75 life (the time taken for the brightness to decay to 75% of the initial brightness) and initial brightness of the red, green and blue primary color OLED device of Example 1 of the present invention, wherein (a) is a red light device, (b) is a green light device, and (c) is a blue light device. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0027] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0028] Example 1
[0029] In this embodiment, the sheet-like organic single crystal 1,4-bis(4-methylphenylvinyl)benzene (BSB-Me) obtained by physical vapor transport method is used as the dual functional layer of charge transport and water and oxygen barrier of the red, green and blue primary color OLED device, and the high carrier mobility and water and oxygen barrier performance of the organic single crystal are utilized to realize a high-efficiency and long-life red, green and blue primary color OLED.
[0030] The method for preparing a three-primary-color OLED device based on an organic single crystal double-functional layer comprises the following steps:
[0031] (1) Growth and preparation of BSB-Me organic single crystals:
[0032] First, place 5 mg of BSB-Me powder in the high-temperature sublimation area of a dual-temperature zone quartz tube furnace; then introduce high-purity argon gas into the tube furnace as a carrier gas to transport the sublimated material to the crystallization area, and the carrier gas flow rate is stabilized at 36 mL / min; set the growth parameters of the tube furnace, the temperatures of the high-temperature sublimation zone and the low-temperature crystallization zone are 270°C and 240°C respectively, and the growth time is 150 minutes, and start growing organic single crystal materials; after growth based on the physical vapor transport method (PVT), thin flake organic single crystal materials will be obtained on the quartz tube wall.
[0033] (2) Preparation of hydrophobic Si substrate:
[0034] First, a single-sided polished Si substrate with a size of 1.4 cm×1.6 cm was ultrasonically cleaned with acetone, ethanol, and isopropanol for 30 minutes in sequence, and then the residual solvent on the surface was blown away with high-pressure nitrogen; then the Si substrate was placed in a culture dish, and 30 μL of octadecyltrichlorosilane (OTS) was taken with a pipette and dropped in the center of the culture dish, which was then sealed with a cover; next, the entire culture dish was placed in a vacuum oven with a vacuum degree of 0.1 MPa, a temperature set to 60°C, and a treatment time of 4 hours, so that OTS was volatilized by heat and the Si substrate was hydrophobicized; finally, the Si substrate that had completed the hydrophobic treatment was ultrasonically cleaned with acetone, ethanol, and isopropanol for 30 minutes in sequence, and the solvent was blown dry with high-pressure nitrogen for later use.
[0035] (3) Water vapor transmission rate test of organic single crystal:
[0036] The BSB-Me organic single crystal grown in step (1) was transferred to the hydrophobic Si substrate treated in step (2); the substrate with the organic single crystal attached was then placed in a vacuum evaporator, and the vacuum reached 5×10 -4 After Pa, a Ca electrode is evaporated on the organic single crystal material through a mask with a thickness of 100 nm and a deposition rate of Then the mask was replaced and the Ag electrode was evaporated to a thickness of 80 nm at a deposition rate of Next, the device was taken out of the vacuum evaporator, and NOA63 photoresist was dripped onto the surface of the device and covered with a glass sheet to press tightly. After the photoresist diffused to the edge of the entire glass, the device was exposed to ultraviolet light for 15 minutes to solidify the photoresist. The device was then peeled off from the substrate with a blade and transferred to a glass substrate, so that the BSB-Me single crystal could cover the Ca electrode and encapsulate it. Figure 1 (a) shows the device structure of the calcium corrosion electrical test. Subsequently, the conductivity of the Ca electrode was monitored under constant temperature and humidity conditions of 30°C and 40% relative humidity, so that the water vapor permeability of the organic single crystal film could be calculated.
[0037] (4) Preparation of red, green and blue primary color OLED devices based on BSB-Me single crystal hole transport layer:
[0038] The BSB-Me organic single crystal grown in step (1) was transferred to the hydrophobic Si substrate treated in step (2); the wafer was placed in a vacuum coating apparatus after being covered with an organic mask, and the vacuum degree reached 5×10 -4 After Pa, the light-emitting layer, hole blocking layer and electron transport layer are sequentially evaporated. The three primary color light-emitting layers are red light (mCP and 5% wt Ir(MDQ)2(acac)), green light (mCP and 5% wt Ir(ppy)2(acac)) and blue light (mCBCP and 5% wtFIrPic). Among them, the blue light device needs to introduce a 10nm hole blocking layer BTSiTrz to block holes, the electron transport layer is Bphen, the thickness of the light-emitting layer and the electron transport layer are 40nm and 40nm respectively, and the deposition rates are and Then, the cathode mask was replaced and the Ca / Ag composite electrode was evaporated to a thickness of 3 nm and 80 nm, respectively, at deposition rates of and Next, NOA63 photoresist was dripped onto the surface of the device and covered with a glass sheet to press tightly. After the photoresist diffused to the edge of the entire glass, the device was exposed to ultraviolet light for 15 minutes to solidify the photoresist. The device was then peeled off from the substrate with a blade and transferred to a glass substrate. The device was then placed in a vacuum evaporator again, covered with an anode mask, and MoO3 and Au / Ag composite electrodes were evaporated in sequence with thicknesses of 5nm and 0.8nm / 8nm, respectively. The deposition rates were controlled to be and Schematic diagram of the structure of OLED device based on the three primary colors of red, green and blue Figure 2 As shown, Figure 2(a) is a red light device, (b) is a green light device, and (c) is a blue light device. The preparation of red, green and blue primary color OLED devices based on BSB-Me single crystal hole transport layer was completed, and then the electroluminescent performance and device life of the device were tested.
[0039] Example 2
[0040] The method for preparing a three-primary-color OLED device based on an organic single crystal double-functional layer comprises the following steps:
[0041] (1) Growth and preparation of 2,6-diphenylanthracene (DPA) organic single crystal materials:
[0042] First, place 4 mg of DPA powder in the high-temperature sublimation area of a dual-temperature zone quartz tube furnace; then introduce high-purity argon gas as a carrier gas into the tube furnace to transport the sublimated material to the crystallization area, and the carrier gas flow rate is stabilized at 30 mL / min; set the growth parameters of the tube furnace, the temperatures of the high-temperature sublimation zone and the low-temperature crystallization zone are 300°C and 270°C respectively, and the growth time is 2 hours, and start growing organic single crystal materials; after growth based on the physical vapor transport method (PVT), thin flake organic single crystal materials will be obtained on the quartz tube wall.
[0043] (2) Preparation of hydrophobic Si substrate:
[0044] First, a single-sided polished Si substrate with a size of 1.4 cm×1.6 cm was ultrasonically cleaned with acetone, ethanol, and isopropanol for 30 minutes in sequence, and then the residual solvent on the surface was blown away with high-pressure nitrogen; then the Si substrate was placed in a culture dish, and 20 μL of octadecyltrichlorosilane (OTS) was taken with a pipette and dropped in the center of the culture dish, which was sealed with a cover; next, the entire culture dish was placed in a vacuum oven with a vacuum degree of 0.1 MPa, a temperature set to 60°C, and a treatment time of 4 hours, so that OTS was volatilized by heat and the Si substrate was hydrophobicized; finally, the Si substrate that had completed the hydrophobic treatment was ultrasonically cleaned with acetone, ethanol, and isopropanol for 30 minutes in sequence, and the solvent was blown dry with high-pressure nitrogen for use.
[0045] (3) Water vapor transmission rate test of organic single crystal:
[0046] The DPA organic single crystal grown in step (1) was transferred to the hydrophobic Si substrate treated in step (2); the substrate with the organic single crystal attached was then placed in a vacuum evaporator, and the vacuum reached 5×10 -4 After Pa, a Ca electrode is evaporated on the organic single crystal material through a mask with a thickness of 100 nm and a deposition rate of Then the mask was replaced and the Ag electrode was evaporated to a thickness of 80 nm at a deposition rate of Next, the device was taken out of the vacuum evaporator, and NOA63 photoresist was dripped on the surface of the device and covered with a glass sheet to press tightly. After the photoresist diffused to the edge of the entire glass, the device was exposed to ultraviolet light for 18 minutes to solidify the photoresist; then the device was peeled off from the substrate with a blade and transferred to a glass substrate, so that the DPA single crystal could cover the Ca electrode and encapsulate it. The conductivity of the Ca electrode was monitored under constant temperature and humidity conditions, and the water vapor permeability of the organic single crystal film was calculated.
[0047] (4) Preparation of red, green and blue primary color OLED devices based on DPA single crystal hole transport layer:
[0048] The DPA organic single crystal grown in step (1) is transferred to the hydrophobic Si substrate treated in step (2); after covering with an organic mask, the wafer is placed in a vacuum coating apparatus and the vacuum degree reaches 5×10 -4 After Pa, the light-emitting layer, hole blocking layer and electron transport layer are sequentially evaporated. The three primary color light-emitting layers are red light (mCP and 4% wt Ir(MDQ)2(acac)), green light (mCP and 4% wt Ir(ppy)2(acac)) and blue light (mCBCP and 4% wtFIrPic). Among them, the blue light device needs to introduce a 10nm hole blocking layer BTSiTrz to block holes, the electron transport layer is TPBi, the thickness of the light-emitting layer and the electron transport layer are 50nm and 50nm respectively, and the deposition rates are and Then, the cathode mask was replaced and the Ca / Ag composite electrode was evaporated to a thickness of 5 nm and 100 nm at deposition rates of and Next, NOA63 photoresist was dripped onto the surface of the device and covered with a glass sheet to press tightly. After the photoresist diffused to the edge of the entire glass, the device was exposed to ultraviolet light for 20 minutes to solidify the photoresist. The device was then peeled off from the substrate with a blade and transferred to a glass substrate. The device was then placed in a vacuum evaporator again, covered with an anode mask, and MoO3 and Au / Ag composite electrodes were evaporated in sequence with thicknesses of 5nm and 0.8nm / 8nm, respectively. The deposition rates were controlled to be and Complete the preparation of red, green and blue primary color OLED devices based on DPA single crystal hole transport layer.
[0049] Example 3
[0050] The method for preparing a three-primary-color OLED device based on an organic single crystal double-functional layer comprises the following steps:
[0051] (1) Growth and preparation of BP1T organic single crystal materials:
[0052] First, place 3 mg of BP1T powder in the high-temperature sublimation area of a dual-temperature zone quartz tube furnace; then introduce high-purity argon gas as a carrier gas into the tube furnace to transport the sublimated material to the crystallization area, and the carrier gas flow rate is stabilized at 40 mL / min; set the growth parameters of the tube furnace, the temperatures of the high-temperature sublimation zone and the low-temperature crystallization zone are 330°C and 280°C respectively, and the growth time is 2h, and start growing organic single crystal materials; after growth based on the physical vapor transport method (PVT), thin flake organic single crystal materials will be obtained on the quartz tube wall.
[0053] (2) Preparation of hydrophobic Si substrate:
[0054] First, a single-sided polished Si substrate with a size of 1.4 cm×1.6 cm was ultrasonically cleaned with acetone, ethanol, and isopropanol for 30 minutes in sequence, and then the residual solvent on the surface was blown away with high-pressure nitrogen; then the Si substrate was placed in a culture dish, and 30 μL of octadecyltrichlorosilane (OTS) was taken with a pipette and dropped in the center of the culture dish, which was then sealed with a cover; next, the entire culture dish was placed in a vacuum oven with a vacuum degree of 0.1 MPa, a temperature set to 60°C, and a treatment time of 4 hours, so that OTS was volatilized by heat and the Si substrate was hydrophobicized; finally, the Si substrate that had completed the hydrophobic treatment was ultrasonically cleaned with acetone, ethanol, and isopropanol for 30 minutes in sequence, and the solvent was blown dry with high-pressure nitrogen for later use.
[0055] (3) Water vapor transmission rate test of organic single crystal:
[0056] The BP1T organic single crystal grown in step (1) was transferred to the hydrophobic Si substrate treated in step (2); the substrate with the organic single crystal attached was then placed in a vacuum evaporator until the vacuum degree reached 5×10 -4 After Pa, a Ca electrode is evaporated on the organic single crystal material through a mask with a thickness of 100 nm and a deposition rate of Then the mask was replaced and the Ag electrode was evaporated to a thickness of 80 nm at a deposition rate of Next, the device was taken out of the vacuum evaporator, and NOA63 photoresist was dripped on the surface of the device and covered with a glass sheet to press tightly. After the photoresist diffused to the edge of the entire glass, the device was exposed to ultraviolet light for 20 minutes to solidify the photoresist; then the device was peeled off from the substrate with a blade and transferred to a glass substrate, so that the BP1T single crystal could cover the Ca electrode and encapsulate it. The conductivity of the Ca electrode was monitored under constant temperature and humidity conditions, so that the water vapor permeability of the organic single crystal film could be calculated.
[0057] (4) Preparation of red, green and blue primary color OLED devices based on BP1T single crystal hole transport layer:
[0058] The BP1T organic single crystal material grown in step (1) was transferred to the hydrophobic Si substrate treated in step (2); the wafer was placed in a vacuum coating apparatus after being covered with an organic mask, and the vacuum degree reached 5×10 -4 After Pa, the light-emitting layer, hole blocking layer and electron transport layer are sequentially evaporated. The three primary color light-emitting layers are red light (CBP and 3% wt Ir(MDQ)2(acac)), green light (mCP and 3% wtIr(ppy)2(acac)) and blue light (mCBCP and 3% wtFIrPic). Among them, the blue light device needs to introduce a 10nm hole blocking layer 2-(3'-(9,9-dimethyl-9H-fluorene-2-yl)-[1,1'-biphenyl]-3-yl)-4,6-diphenyl-1,3,5-triazine to block holes. The electron transport layer is TmPyPB. The thickness of the light-emitting layer and the electron transport layer are 40nm and 40nm, respectively. The deposition rates are and Then, the cathode mask was replaced and the Ca / Ag composite electrode was evaporated to a thickness of 3 nm and 80 nm, respectively, at deposition rates of and Next, NOA63 photoresist was dripped onto the surface of the device and covered with a glass sheet to press tightly. After the photoresist diffused to the edge of the entire glass, the device was exposed to ultraviolet light for 15 minutes to solidify the photoresist. The device was then peeled off from the substrate with a blade and transferred to a glass substrate. The device was then placed in a vacuum evaporator again, covered with an anode mask, and MoO3 and Au / Ag composite electrodes were evaporated in sequence with thicknesses of 5nm and 0.8nm / 8nm, respectively. The deposition rates were controlled to be and Complete the preparation of red, green and blue primary color OLED devices based on BSB-Me single crystal hole transport layer.
[0059] Through the performance measurement of Example 1, we can understand that:
[0060] Figure 1 (b) is the normalized conductivity curve of the calcium electrode over time, which is the conductivity curve of the calcium electrode based on organic single crystal encapsulation under constant temperature and humidity conditions of 30°C and 40% relative humidity, and the calcium corrosion electrical test is carried out over time. The water vapor permeability of the organic single crystal film is calculated by formula (1):
[0061] WVTR=-n·M(H2O) / M(Ca)δ Ca ·ρ Ca ·L / a·d(1 / R) / dt (1);
[0062] Where n represents the reaction ratio of H2O and Ca, which is 2; M(H2O) and M(Ca) represent the molar masses of H2O and Ca, which are 18 g / mol and 40 g / mol, respectively; δ Ca is the density of Ca, which is 1.55 g / cm 3 ρ Ca represents the resistivity of Ca, and its value is 3.91Ω·m; L and α represent the length and width of the calcium electrode, which are 0.5 mm and 1 mm respectively; R is the resistance of the calcium electrode.
[0063] The water vapor permeability of the organic single crystal film is 3.58×10 -4 grams / square meter / day, showing excellent water and oxygen barrier properties, indicating that the organic single crystal can act as a water and oxygen barrier layer inside the device to prevent other organic functional layers from being corroded by water and oxygen.
[0064] Figure 3 is the electroluminescent performance diagram of the red, green and blue primary color OLED device prepared in Example 1. Figure 3 As can be seen from (a), (b), and (c), the red, green, and blue primary color OLED device prepared in Example 1 exhibits high-efficiency electroluminescent performance. The maximum brightness of the red OLED is 25370 candelas per square meter, the maximum current efficiency is 22.89 candelas per ampere, and the maximum external quantum efficiency is 13.78%; the maximum brightness of the green OLED is 86380 candelas per square meter, the maximum current efficiency is 49.12 candelas per ampere, and the maximum external quantum efficiency is 12.50%; the maximum brightness of the blue OLED is 20100 candelas per square meter, the maximum current efficiency is 16.05 candelas per ampere, and the maximum external quantum efficiency is 7.80%.
[0065] Figure 4 The luminance decay curves of the red, green and blue primary color OLED devices prepared in Example 1 at different initial brightnesses are shown. All devices show good stability. Among them, the red light OLED has an initial brightness of 8506, 5087 and 3687 candela per square meter, and its LT75 life (the time taken for the brightness to decay to 75% of the initial brightness) is 50.2, 123.0 and 198.1 hours respectively; the green light OLED has an initial brightness of 9144, 5508 and 3549 candela per square meter, and its LT75 life is 37.1, 114.4 and 305.1 hours respectively; the blue light OLED has an initial brightness of 8641, 4875 and 2328 candela per square meter, and its LT75 life is 25.5, 72.9 and 257.3 hours respectively. Through fitting, the relationship between the life and initial brightness of the red, green and blue primary color OLED devices prepared in Example 1 can be obtained.
[0066] Figure 5 The LT75 life (the time taken for the brightness to decay to 75% of the initial brightness) and the initial brightness of the red, green and blue primary color OLED device of Example 1 are fitted by the empirical formula (2):
[0067]
[0068] Where L0 is the starting brightness, n is the acceleration factor, τ is the lifetime, and C is a constant. At a brightness of 1000 candela per square meter, the LT75 lifetimes of the red, green, and blue devices are 1637, 5105, and 1153 hours, respectively.
[0069] Therefore, the present invention adopts the above-mentioned three-primary color OLED device based on organic single crystal dual-functional layer and its preparation method, replaces the traditional evaporated amorphous film with organic single crystal semiconductor material, uses red, green and blue three-primary color luminescent film as the luminescent layer, and uses the high mobility and excellent water and oxygen barrier performance of organic single crystal to play the dual functional layer role of charge transfer layer and water and oxygen barrier layer in the device, thereby improving the current efficiency and stability of the OLED device.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a three-primary color OLED device based on an organic single crystal dual-functional layer, characterized in that: The steps include: S1. Growth and preparation of organic single crystals. 3-5 mg of organic single crystal material powder is placed in the high-temperature sublimation area of the dual-temperature zone quartz tube furnace. Then, high-purity argon gas is introduced into the tube furnace as a carrier gas to transport the sublimated material to the crystallization area. The temperature of the high-temperature sublimation zone and the low-temperature crystallization zone of the tube furnace, as well as the growth time, are set to start growing the organic single crystal material. After growth based on the physical vapor transport method, a thin sheet of organic single crystal material is obtained on the quartz tube wall. S2, substrate pretreatment, after the substrate is ultrasonically cleaned with a cleaning agent, the solvent on the surface is blown away with high-pressure nitrogen, and then the cleaned substrate is placed in a culture dish, a hydrophobic modifier is dripped in the center of the culture dish, and the culture dish cover is closed, and the culture dish is placed in a vacuum oven to volatilize the hydrophobic modifier by heat and perform surface hydrophobic treatment on the substrate, and the treated substrate is taken out and ultrasonically cleaned with a cleaning agent again, and the solvent is blown away with high-pressure nitrogen and then set aside; S3, water vapor permeability test of organic single crystal material, the thin sheet organic single crystal material grown in step S1 is transferred to the substrate pre-treated by hydrophobic treatment in step S2 with tweezers, and then the substrate with the organic single crystal attached is placed in a vacuum evaporation apparatus, Ca electrode is evaporated on the organic single crystal material through a mask, and then the mask is replaced, Ag electrodes are evaporated on both sides of the Ca electrode, so that the Ag electrodes on both sides are connected through the middle Ca electrode, the substrate is taken out of the vacuum evaporation apparatus, and photoresist is dripped on the surface of the substrate and covered with a transfer glass sheet for pressing, after the photoresist diffuses and covers the entire substrate, the substrate is placed under ultraviolet light for exposure to solidify the photoresist, and then the device is peeled off from the hydrophobic substrate with a blade and transferred to the glass substrate, the organic single crystal material can cover the Ca electrode and encapsulate it, the conductivity of the Ca electrode is tested under constant temperature and humidity conditions, and the water vapor permeability of the organic single crystal material is calculated; S4. Preparation of red, green and blue primary color OLED devices based on organic single crystal charge transport layer. The thin sheet organic single crystal material grown in step S1 is transferred to the hydrophobic pretreated substrate in step S2 with tweezers, and the substrate with organic single crystal is covered with an organic layer mask, and placed in a vacuum evaporator. The light-emitting layer, hole blocking layer and electron transport layer are deposited on the organic single crystal material by vacuum thermal evaporation in sequence, and the cathode mask is replaced to continue to deposit the cathode. The device is taken out of the vacuum evaporator, and photoresist is dripped on the surface of the device and covered with a transfer glass sheet to press tightly. After the photoresist diffuses and covers the entire device, the device is exposed to ultraviolet light to solidify the photoresist. Subsequently, the device is peeled off from the hydrophobic substrate with a blade and transferred to a glass substrate. The device is then covered with an anode mask and placed in a vacuum evaporator. The hole injection layer and the anode are evaporated in sequence to complete the preparation of the entire device.
2. The method for preparing a three-primary-color OLED device based on an organic single crystal dual-functional layer according to claim 1, characterized in that: In step S1 , the organic single crystal material is a p-type organic single crystal semiconductor material.
3. The method for preparing a three-primary-color OLED device based on an organic single crystal dual-functional layer according to claim 2, characterized in that: The organic single crystal material is one of 1,4-bis(4-methylphenylvinyl)benzene, 2,6-diphenylanthracene and 2,5-bis(4-biphenyl)thiophene.
4. The method for preparing a three-primary-color OLED device based on an organic single crystal dual-functional layer according to claim 1, characterized in that: In step S1, the temperature of the sublimation zone and the crystallization zone of the dual-temperature zone tubular furnace are 270-380° C. and 240-340° C. respectively, the growth time is 2-3 hours, and the flow rate is 30-40 mL / min.
5. The method for preparing a three-primary-color OLED device based on an organic single crystal dual-functional layer according to claim 1, characterized in that: In step S2, the substrate is a single-side polished Si substrate with a size of 1.4 cm×1.6 cm, the cleaning agents are acetone, ethanol and isopropanol, the hydrophobic modifier is octadecyltrichlorosilane, the modification temperature is 60° C., the time is 4 hours, and the vacuum degree of the vacuum oven is 0.1 MPa.
6. The method for preparing a three-primary-color OLED device based on an organic single crystal dual-functional layer according to claim 1, characterized in that: In step S3, the Ca electrode evaporation rate is The evaporation rate of Ag electrode is The exposure and curing time of the photoresist under UV light is 15-20 minutes.
7. The method for preparing a three-primary-color OLED device based on an organic single crystal dual-functional layer according to claim 1, characterized in that: In step S4, the light-emitting layer includes red, green and blue primary color organic light-emitting materials and a main body material; the hole blocking layer is one of 2-(4-(dibenzo[b,d]thiophene-4-yldiphenylsilyl)phenyl)-4,6-diphenyl-1,3,5-triazine and 2-(3'-(9,9-dimethyl-9H-fluorene-2-yl)-[1,1'-biphenyl]-3-yl)-4,6-diphenyl-1,3,5-triazine; the electron transport layer is one of 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene, 4,7-diphenyl-1,10-phenanthroline and 3,3'-[5'-[3-(3-pyridyl)phenyl][1,1':3',1"-terphenyl]-3,3"-diyl]bipyridine, and the evaporation rate is The cathode is a Ca / Ag composite electrode, and the evaporation rates are and The hole injection layer is MoO3, and the evaporation rate is The anode is a composite electrode of Au and Ag, and the evaporation rate is 8. The method for preparing a three-primary-color OLED device based on an organic single crystal dual-functional layer according to claim 7, characterized in that: The red light organic light emitting material is bis(2-methyldibenzo[F,H]quinoxaline)(acetylacetonate)iridium(III), the green light organic light emitting material is acetylacetonate di(2-phenylpyridine-C2,N)iridium(III), the blue light organic light emitting material is di(4,6-difluorophenylpyridine-C2,N)pyridinecarboxylateiridium(III), the main material is one of 4,4'-bis(N-carbazole)-1,1'-biphenyl, 1,3-bis(N-carbazolyl)benzene, and 9-(3-(9H-carbazole-9-yl)phenyl)-9H-3,9'-dicarbazole, and the red, green and blue organic light emitting materials are doped in the main material at a mass ratio of 1% to 5%, respectively, to prepare an organic phosphorescent film as a light emitting layer.
9. A three-primary-color OLED device based on an organic single crystal and dual-functional layers, prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Testing method for water vapor penetration rate of thin film
CN107449704A
Preparation of three primary color combined white OLED devices using organic single crystal materials and preparation method thereof
CN108649145A
Method for testing water vapor transmittance of packaging film
CN111458277A
OLED device based on organic semiconductor single-crystal charge transfer layer and preparation method thereof
CN116075199A